GROWTH, FRUITING CYCLE AND OOSPORE OUTPUT IN TURBINARIA DECURRENSBORY - Kaliaperumal, N; Rao, M Umamaheswara (Indian Journal of Fisheries, 2011)
iStudies oil the growth, fruiting cycle and oospore output in Turbinaria decurrens, carried out for one year from March 1972 to February 1973 are presented in this papsr. Young plants of T. decurrens, observed in the natural habitats in May and June, grow to maximum size in the period from December to February. Plants with receptacles occur for eleven months from August to June, with large nunibsr of fruiting plants in the peak growth season from December to February. Periodicity was not seen in the liberation of oospores and during the fruiting season peak output erf spores was observed in November. From this study, it is suggested that the period December-January is suitable for harvesting the crop of T. decurrens in the localities around Mandapam.